2021
DOI: 10.1038/s41598-021-86105-5
|View full text |Cite
|
Sign up to set email alerts
|

Haze of glue determines preference of western flower thrips (Frankliniella occidentalis) for yellow or blue traps

Abstract: In a wind tunnel we compared the colour preference for western flower thrips to four types of colour plates (clear, white, blue and yellow) applied with two types of glue (diffuse Stikem versus clear D41). Further the results for blue and yellow preference were validated in two greenhouses. In the wind tunnel, we found a clear preference of yellow over blue when a clear glue (D41) was used. However, with a more diffuse (whitish) glue (Stikem) the preference for yellow over blue disappeared, whereby the attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Amongst these factors, the most obvious relates to methodological differences such as the rearing conditions, the preparation of insects prior to experiments, different experimental apparatus, and different conditions such as temperature, illumination, time of evaluation, duration of experiment, etc. Even the type of glue used on traps can influence the blue and yellow preference of WFT [ 35 ]. However, there are currently no studies that have considered such differences in the methodology as the cause for varying conclusions as to WFT attraction to blue and yellow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst these factors, the most obvious relates to methodological differences such as the rearing conditions, the preparation of insects prior to experiments, different experimental apparatus, and different conditions such as temperature, illumination, time of evaluation, duration of experiment, etc. Even the type of glue used on traps can influence the blue and yellow preference of WFT [ 35 ]. However, there are currently no studies that have considered such differences in the methodology as the cause for varying conclusions as to WFT attraction to blue and yellow.…”
Section: Introductionmentioning
confidence: 99%
“…Two laboratory WFT populations were tested here, reared at Wageningen University and Research (Wageningen, The Netherlands), which had previously shown a higher attraction to yellow compared to other colours including blue [ 35 ], and Leibniz University Hannover (Hannover, Germany), which had independently shown a clear preference for blue compared to other colour cues including yellow [ 15 , 20 ]. The main objective was to observe these two populations in the same wind tunnel facility, under the same experimental conditions and host plant rearing regime to test the hypothesis that the differing response of these populations is independent of the experimental protocol.…”
Section: Introductionmentioning
confidence: 99%
“…The wind tunnel test area and setup were performed as described by van Tol et al (2021). 23 The light condition in the wind tunnel (ceiling illumination) was adapted to a setting for dusk (Fig. 1) and measured as a reflection of light on a spectralon plate.…”
Section: Wind Tunnel Visual Experiments 221 Wind Tunnel Settingsmentioning
confidence: 99%
“…1) and measured as a reflection of light on a spectralon plate. 23 The light spectrum was composed of LEDs in the visible range of 400-750 nm (LED-strip -Full-color RGB + Warm White -24 V High Power Protected 5050, LuxaLight, NL) 23 and a component in the UV-A range of 360 -390 nm (peak at 365 nm)(strip of UV LED Engin, LZ4-04UV00, Osram Sylvania Inc., USA). Furthermore, the humidity (70%), temperature (24 °C), and wind speed (2 cm s -1 ) of the tunnel were conditioned based on the optimal data for flight of western flower thrips.…”
Section: Wind Tunnel Visual Experiments 221 Wind Tunnel Settingsmentioning
confidence: 99%
See 1 more Smart Citation